Phenomenology Of Students' Learning Experiences In The Application Of Deep Learning Strategies In Fiqih Lessons - Isnaini (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
Study This aim For describe in a way deep experience Study student in The application of deep learning strategies in Islamic jurisprudence learning at MA Putri Al- Ishlahuddiny. Research use approach qualitative method phenomenology For understand experience subjective student in a way holistic. Data collected through observation , interview in-depth , and documentation. Research results show that the application of deep learning encourages transformation method Study student from pattern memorization going to understanding more conceptual in-depth. Students experience improvement ability analyze Fiqh cases , connecting material with reality life , and grow motivation and engagement emotional in learning. Deep learning strategies also create learning meaningful in accordance Ausubel's theory and encourages the construction process knowledge as Bruner explained. From the perspective phenomenology , students feel that Fiqh learning becomes more relevant , close with experience personal , and grow spiritual awareness. Research This conclude that deep learning is effective increase quality of process and results study Fiqh as well in line with objective Islamic education for grow understanding deep ( tafaqquh fi ad- dîn ). Findings This expected become references in development design more Islamic jurisprudence learning reflective , contextual , and meaningful.